Application of genome editing tools in plants - Thanh, Nguyen Duc (Vietnam Journal of Biotechnology, 2021)
Genome editing technology is the genome modification techniques, such as targeted mutagenesis or insert/delete/replacement at specific locations in the genome of living organisms. Genome editing is based on the creation of double sequence break (DSB) in a specific location and DNA repair via nonhomologous end joining (NHEJ) or homology direct repair (HDR). The development of sequence-specific nuclease (SSN) allows precise editing of the target gene. These SSNs include: meganuclease (MN), zinc finger nuclease (ZFN), transcription activator-like effector nuclease (TALEN) and CRISPR-associated nuclease (Cas) including CRISPR/Cas9 (from Streptococcus pyogenes) and CRISPR/Cpf1 (from Prevoltella and Francisella1). These are the genome editing tools used to create DSBs at specific locations of the genome. Recently, the base editing (BE) and prime editing (PE) tools have been reported. This review will cover the basics of these tools and their application in genome editing in plants, especially providing the most up-to-date information on their application in crop improvement.